Celastrol increases glucocerebrosidase activity in Gaucher disease by modulating molecular chaperones - Yang, Chunzhang (National Academy of Sciences, 2014)
Gaucher disease is caused by mutations in the glucosidase, beta, acid gene that encodes glucocerebrosidase (GCase). Glucosidase, beta, acid mutations often cause protein misfolding and quantitative loss of GCase. In the present study, we found that celastrol, an herb derivative with known anticancer, anti-inflammatory, and antioxidant activity, significantly increased the quantity and catalytic activity of GCase. Celastrol interfered with the establishment of the heat-shock protein 90/Hsp90 cochaperone Cdc37/Hsp90-Hsp70-organizing protein chaperone complex with mutant GCase and reduced heat-shock protein 90-associated protein degradation. In addition, celastrol modulated the expression of molecular chaperones. Bcl2-associated athanogene 3 and heat shock 70kDa proteins 1A and 1B were significantly increased by celastrol. Furthermore, BAG family molecular chaperone regulator 3 assisted protein folding and maturation of mutant GCase. These findings provide insight into a therapeutic strategy for Gaucher disease and other human disorders that are associated with protein misfolding.